Buckling design of submerged arches via shape parameterization. Issue 5 (9th August 2019) - Hernández‐Díaz, Alejandro Mateo; Muñoz, Andrés; Jiménez‐Alonso, Javier Fernando; Sáez, Andrés
Abstract : Several of the geometric solutions obtained from the funicular design of submerged plane arches reach their critical buckling loads under service conditions. Consequently, the arch geometry must be modified, and then the bending moment increases considerably. Previous works have shown that the funicular shape of a submerged arch is close to either a parabolic or an elliptical form (depending on the water depth, the axial compressive force, and the arch height). In this work, such funicular shape is approximated using a parametric function of these two conical forms. Following this parameterization, the arch shape is optimized via an evolutionary algorithm taking into account its geometrically nonlinear behavior. As a result, the optimized shape shows a significative reduction in the second‐order bending stresses, due to a redistribution of the internal forces along the arch length. These results may find interesting applications in the optimal structural design of, among others, recreational underwater installations.